6x+1 / 2x +6 - 5/2
Factor 2 out of the denominator of the first fraction:
6x+1 / 2(x+3) - 5/2
Rewrite 5/2 to have a common denominator with the first fraction:
6x+1/2(x+3) - 5(x+3) / 2(x+3)
Simplify terms:
6x +1 - 5(x+3) / 2(x+3)
Use distributive property:
6x +1 - 5x -15 / 2(x+3)
Combine like terms for final answer:
(x-14) / 2(x+3)
Answer:
y = 3x - 5
Step-by-step explanation:
y = mx + b
m (slope) = 3/1 or 3
b (y-intercept) = -5
y = 3x - 5
-5 and -4.
-5 times -4 is 20 while adding -5 and -4 it equals -9. (don't be very harsh if i got this wrong)